2016
DOI: 10.1089/biores.2016.0020
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Preliminary In Vitro Investigation of a Magnetic Iron Oxide Nanoparticle Conjugated with Ligand CD80 and VEGF Antibody As a Targeted Drug Delivery System for the Induction of Cell Death in Rodent Osteosarcoma Cells

Abstract: Target drug deliveries using nanotechnology are a novel consideration in the treatment of cancer. We present herein an in vitro mouse model for the preliminary investigation of the efficacy of an iron oxide nanoparticle complex conjugated to vascular endothelial growth factor (VEGF) antibody and ligand cluster of differentiation 80 (CD80) for the purpose of eventual translational applications in the treatment of human osteosarcoma (OSA). The 35 nm diameter iron oxide magnetic nanoparticles are functionalized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This suggested that the imbalance expression profile of cytokines and chemokines might contribute to the homeostatsis disturbances in systemic environments and disease progression of osteosarcoma. Due to the well‐understood function and being the potential therapeutic target of VEGF for osteosarcoma , we chose CXCL8 as the targeting chemokine for further analyses to improve the understanding of immunopathogenesis of osteosarcoma. CXCL8, which is also known as IL‐8, is a chemokine produced by various cell types, and mainly plays a proinflammatory role by recruitment and activation of neutrophils/granulocytes to the site of infection or tissue injury .…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the imbalance expression profile of cytokines and chemokines might contribute to the homeostatsis disturbances in systemic environments and disease progression of osteosarcoma. Due to the well‐understood function and being the potential therapeutic target of VEGF for osteosarcoma , we chose CXCL8 as the targeting chemokine for further analyses to improve the understanding of immunopathogenesis of osteosarcoma. CXCL8, which is also known as IL‐8, is a chemokine produced by various cell types, and mainly plays a proinflammatory role by recruitment and activation of neutrophils/granulocytes to the site of infection or tissue injury .…”
Section: Discussionmentioning
confidence: 99%
“…However, the drawback of most existing HCC-targeted MRI molecular probes is that the singularity of the target may weaken the detection specificity and sensitivity, considering the tumor heterogeneity and false positive or false negative diagnoses associated with cancer biomarkers. Therefore, a more complex targeted probe design such as double antigen-targeted probes are well appreciated to precisely capture the molecular features of tumors[22,23] and, hence, are expected to further enhance the precision and imaging quality of small HCC or MHCC lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial growth factor (VEGF) antibody was chosen as the targeted agent for the elevated production of VEGF antigen in OS cells (43), which plays a significant role in tumor angiogenesis processes. For the treatment of OS, an iron oxide nanoparticle complex conjugated to VEGF antibody and the ligand cluster of differentiation 80 (CD80) was developed (44). This combination approach would be able to target not just the extensively expressed VEGF antigen in OS cells, but also the increased expression of the surface cell receptor cytotoxic T lymphocyteassociated antigen-4 (CTLA4) (44).…”
Section: Antibodies As Targeting Ligandsmentioning
confidence: 99%
“…For the treatment of OS, an iron oxide nanoparticle complex conjugated to VEGF antibody and the ligand cluster of differentiation 80 (CD80) was developed (44). This combination approach would be able to target not just the extensively expressed VEGF antigen in OS cells, but also the increased expression of the surface cell receptor cytotoxic T lymphocyteassociated antigen-4 (CTLA4) (44).…”
Section: Antibodies As Targeting Ligandsmentioning
confidence: 99%